Topology optimization of blank holders based on a kriging-interpolated level-set method. Issue 4 (3rd April 2021) - Xie, Yanmin; Guo, Yuanheng; Zhang, Fei; Wang, Dongtao
ABSTRACT: Blank holders play an important role in non-isothermal stamping, and blank holder optimization is thus investigated in this article. A kriging-interpolated level-set method based on a parallel infilling strategy is proposed. First, a new method is used to discretize the design domain of a blank holder. The first-stage kriging model between the nodes and level-set values is developed, and a new blank holder structure can be determined according to a level-set threshold. The second-stage kriging model between the level sets and forming quality is then developed. The second-stage kriging model is updated based on a parallel infilling strategy. The best level-set values are obtained via an improved particle swarm optimization, and the optimal blank holder structure is determined. The proposed method is validated using a cross-shaped part. The results show that the optimized blank holder mass is reduced by 28%, and the forming quality is improved significantly.